Organizational Change via Social Hubs: A Computer Simulation Based Analysis - Demir, Kadir Alpaslan; Ozkan, Baris Egemen (Elsevier Science Bv, 2015)
Organizational change is a risky and challenging endeavor for any type of organization. There are many aspects to change management and one important aspect is persuasion. Persuasion helps to implement a successful change management program. A social hub is person who has social ties to many other people compared to most people. In popular culture, this type of person is also called a popular person. In organizations, there are popular employees who are in fact a social hub. These employees have influence on other employees and they can persuade others towards a particular belief. In this paper, we investigate the role of persuasive social hubs for organizational change. We believe persuasive social hubs can be used to achieve organizational change. In social studies, it is hard to replicate conditions and isolate certain factors. Therefore, in this paper, we benefit from computer simulations and isolate the effect of persuasion by stabilizing all other factors. Our analysis revealed that using social hubs increase the chance of success in organizational change.
4th International Conference on Leadership, Technology, Innovation and Business Management (ICLTIBM) -- NOV 19-21, 2014 -- Istanbul, TURKEY
Keywords: Change Management; Organizational Change; Social Hub; Persuasion; Change; Computer Simulation; Popular Employee; Organization